The use of recycled plastic in concrete. An alternative to reduce the ecological footprint - Sanchez Soloaga, Iris; Oshiro, Angel; Positieri, Maria (Revista de la Construcción. Journal of Construction, 2014)
The concrete in its production emits gases into the atmosphere causing an environmental impact, however reducing their consumption should not be the best approach to this problem as it could affect the economic development of a region or country. The solution is in the design sustainable material. The Ecological Footprint (EF) to estimate the resource consumption and waste assimilation of a given population, expressed in area of productive land. This paper presents the calculation of a concrete EF located in CórdobaArgentina, the area required to meet the estimated consumption associated with the materials used in the concrete with incorporation of plastics as a replacement of coarse aggregate, as a contribution to protecting the environment. To conclude, the aggregates occupying the largest volume in the preparation of concrete have a small environmental load in proportion to the EF of all the materials used, affecting only 8%. This is because the release rates of CO2 in the most significant overall footprint are mainly concrete cement content. However, the use of plastic waste in the concrete, will provide environmental benefits.